2012
DOI: 10.1039/c2mt20149f
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cerium oxide nanoparticles on tomato (Solanum lycopersicum L.) and its implications for food safety

Abstract: Sustainable development of nanotechnology requires an understanding of the long term ecotoxicological impact of engineered nanomaterials on the environment. Cerium oxide nanoparticles (CeO₂-NPs) have great potential to accumulate and adversely affect the environment owing to their widespread applications in commercial products. This study documented the chronic phenotypic response of tomato plants to CeO₂-NPs (0.1-10 mg L⁻¹) and determined the effect of CeO₂-NPs on tomato yield. The results indicated that CeO₂… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
160
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(172 citation statements)
references
References 35 publications
8
160
3
1
Order By: Relevance
“…Interestingly, the authors included an aerial exposure on leaves and although nanoceria could not be washed from the tissue, the particles were not internalized or transferred to new growth. Similarly, Wang et al 81 grew tomato in the presence of nanoceria-amended (0.1-10 mg/l) irrigation water and reported either no impact or slight enhancements in plant growth and yield. The authors did observe ceria in the shoots, including edible tissues, which suggests translocation, but the mechanism and form of element transfer is unknown.…”
Section: Soil Exposures In Plantsmentioning
confidence: 96%
“…Interestingly, the authors included an aerial exposure on leaves and although nanoceria could not be washed from the tissue, the particles were not internalized or transferred to new growth. Similarly, Wang et al 81 grew tomato in the presence of nanoceria-amended (0.1-10 mg/l) irrigation water and reported either no impact or slight enhancements in plant growth and yield. The authors did observe ceria in the shoots, including edible tissues, which suggests translocation, but the mechanism and form of element transfer is unknown.…”
Section: Soil Exposures In Plantsmentioning
confidence: 96%
“…10 NP sizes above active transport ranging from 14 to 40 nm had a large variation in uptake ranging from 0.25 to 3750 μg/g of plant, but typically had accumulation ranging from ∼1−1100 μg/g of plant again with the majority of the NPs contained within the root and with 0.5−183 μg/g in the leaves. 1,15,16,20,27,29 NPs (50 nm), had accumulation in mung bean of 8 μg/g and in wheat of 32 μg/ g. 32 When comparing the accumulation of two similarly sized TiO 2 -NPs of different crystalline structure [22 nm (rutile) and 25 nm (anatase)] in wheat different accumulation amounts were observed, suggesting size was not the only limiting factor for transportation into a plant. 1 In another study using radioactive NPs, Zhang et al 141 Cemetal could dissolute and be transported into the plant, making it appear as if the intact-NPs were in the plant because possible leaching of radioactivity was not explored.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The authors also included an aerial exposure on leaves, and similarly corn growth was not affected. Wang et al (2012) grew tomato in the presence of CeO 2 NP-amended (0.1-10 mg/L) irrigation water throughout the lifetime of this plant and reported either no impact or slight enhancements in plant growth and yield. A recent study demonstrated that CeO 2 NPs had a modest impact on soybean growth in soil but showed a detrimental impact on the nitrogen fixation bacterial community on soybean roots (Priester et al 2012).…”
Section: Phyto-effect Of Cerium Oxide Nanoparticlesmentioning
confidence: 94%
“…The authors reported that after 14-day exposure with the CeO 2 NPs in the irrigation water (50 mL of 10 μg/mL per day) resulted in no detection of ceria in the leaves or sap of corn plants. In contrast, Wang et al (2012) grew tomato from seeds to the maturity of the plants in the presence of CeO 2 NP-amended (0.1-10 mg/L) irrigation water and reported the detection of ceria in all plant tissues, including tomato fruits, suggesting translocation. Interestingly, the authors also noticed high concentrations of ceria in tomato seeds irrigated with 10 mg/L CeO 2 NP-containing solution than controls.…”
Section: Uptake and Accumulation Of Titanium Dioxidementioning
confidence: 95%